Development of Cloth Notification System for Outdoor Clothesline - Osman, Hafiz Haziq; Tukiran, Zarina; Ismail, Nurulhuda; Juhari, Nurul Ainaa; Aminuddin, Nuramin Fitri (Evolution in Electrical and Electronic Engineering, 2023)
Hanging the cloth at the outdoor clothesline is considered economical because of the use of natural processes to dry the cloth. However, due to a busy lifestyle, the user might forget to lift up the dry cloth which might expose the cloth to rewashing, photodegradation and etcetera. Therefore, in this work, an invention of a prototype to remind the user about their drying cloth is proposed. The proposed notification system consists of two (2) parts namely a sensing and controlling unit and a notification Apps. The sensing and controlling unit consists of a cloth peg that is equipped with a humidity sensor to sense the state of the clothes. When the state of clothes reaches the dry threshold, an ESP32 microcontroller instructs a text message to be displayed on the user’s notification Apps namely the Telegram App. Experimental findings on the functionality of the proposed notification system show the proposed notification system is able to receive and display the alert message whenever the dry threshold is reached. These findings demonstrate that the proposed system gives promising results in assisting the user to estimate and plan when to lift up the clothes.